“MY TONGUE – IS OF THE PEOPLE”: THE PROVERBIAL LANGUAGE OF FRIEDRICH NIETZSCHE’S THUS SPOKE ZARATHUSTRTA - Mieder, Wolfgang (Proverbium - Yearbook, 2013)
Friedrich Nietzsche repeatedly relies on elements of preformulated folk speech to add a certain metaphorical expressiveness to his thoughts and arguments, no matter whether they appear in aphorisms, fragments, poems, letters, essays or entire books. It is then surprising that the considerable secondary literature on Thus Spoke Zarathustra has been almost completely silent on its obvious proverbiality, and this even though Nietzsche occasionally refers with distinct introductory formulas to Bible and folk proverbs employed by him. This might well be due to the fact that Nietzsche seldom cites proverbs in their traditional wording since they would be far too didactic and moralistic for his insistence on the revaluation of all values. Thus he parodies, manipulates, alienates, and contradicts proverbs by changing them into innovative anti-proverbs while at the same time also creating his own pseudo-proverbs to argue for a life free of antiquated rules and regulations. Often he merely alludes to proverbs using their metaphors merely to enhance his expressive style without any agreement with their wisdom. After all, Nietzsche wants to show how everything is something becoming and not an end, and that the positive struggle with fate has to be undertaken in eternal return (repetition) without rigid guidelines as proverbs would be. In any case, proverbial matters accompany Zarathustra on his path towards self-recognition and the acceptance of life. The numerous proverbial expressions with their metaphors add much to the poetic style of Thus Spoke Zarathustra, while the usually varied Bible and folk proverbs are used to underscore the break with God and Christianity. There is no doubt that the message of this literary and philosophical work is to a considerable degree in-formed by the multifaceted nuances of its proverbial language.